“BRIKET CATTAPA” ALTERNATIF BRIKET BIOARANG TERBARUKAN BERBAHAN BUAH KETAPANG (TERMINALIA CATTAPA) YANG RAMAH LINGKUNGAN - Nurul Hidayah; Iin Astarinugrahini; Lulu Maklunah (Pelita - Jurnal Penelitian Mahasiswa UNY, 2014)
AbstractThis study is conducted to find out how to make ketapang (Terminaliacattapa)fruit-based charcoal briquettes and to reveal the effectiveness testing of its quality.The briquettes called cattapa briquettes were made from the charcoal of the ketapang(Terminaliacattapa) with the material ratio of 3: 1. The briquettes were then shapedand pressed with a special tool and dried under the sun for about 2-5 hours. Thequality of cattapa briquettes was tested in two stages, namely testing the watercontent testing and the fuel testing. The results of the analysis on the calculation of thelevels of water reduction show that the cattapa briquettes has a water contentreduction as much as 58.38%, while the results of the fuel testing show that cattapabriquettes are less effective and the quality is not good.